Bilateral Congenital Absence of the Stapes Superstructure in Two Siblings. (22nd June 2014) - Undabeitia, Jose Ignacio; Undabeitia, José; Cianci, Laura; Padilla, Luis; Petreñas, Eduardo; Municio, Antonio
Abstract : Middle ear ossicle malformations are an uncommon event. Among them, the congenital absence of the stapes is a very rare condition that is seldom described in the literature. We report the cases of two women, aged 19 and 22, who presented with a long history of conductive deafness. An exploratory tympanotomy was performed and the absence of the stapes superstructure and an abnormal position of the facial nerve could be observed. A bone anchored hearing aid (BAHA) was implanted in both patients with good results. It is believed that stapes agenesis is related to an abnormal development of the facial nerve, which by the 5th to 6th week of gestation would interpose between the otic capsule and the stapes blastema, preventing these structures from contacting. A long history of nonprogressive hearing loss from birth or early childhood is the key to reach a diagnosis. Several treatment options have been described. The authors opted for a hearing aid due to the high risk of facial nerve lesion, with good functional results.